Bahasa Gaul di Media Sosial: Kajian Morfologi - Audina, Fitra; Aspinda, Lili; Nasution, Safira Ulya; Astuti, Widia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the use of slang on social media as well as its relation to standard language. Methodology used is qualitative descriptive with data analysis techniques in the form of observation and field records. The theory used in this study is linguistic theory, especially morphology and syntax theory. The results of the research show that the use of slang on social media has a connection with standard language, both in terms of morphology and syntax. Although slang contains many words of absorption from foreign languages and uses many abbreviations or acronyms, but their use has its own rules that follow Indonesian structure in general. Therefore, slang on social media can be considered a form of variety or language style used by society in social interaction on social media. Keywords:Method, social media, Lengguage